Missionaries, migrants, and the Manyika: The invention of ethnicity in Zimbabwe - Ranger, Terence (My University, 1984)
Over the last twenty years there have been all too many conflicts in Zimbabwean African politics - conflicts between and within African parties and guerrilla movements, divisions amongst voters, strains within the cabinet of the government of independent Zimbabwe. There have also arisen a number of schools of interpretation of such divisions. Some see them in terms of class conflicts; others however see them in terms of ethnicity. They invoke not only the allegedly 'traditional' hostility of 'the Ndebele' and 'the Shona', but also an asserted conflict between Shona sub-ethnicities, the so-called 'Korekore', 'Zeruru', 'Karanga', 'Kalanga' and 'Manyika’…. Analyses such as these raise two main questions in an historian's mind. The first question, to which I shall return briefly at the end of this chapter, is whether they provide an accurate explanation for recent conflicts. The second question, to which most of this chapter will be devoted, is from where the idea of such entities as the 'Manyika', the 'Zezuru' and the rest has come. These entities certainly do not represent pre-colonial 'historical fact', nor can they in the present be properly described as 'tribes' or 'clans', no matter that both Africans and European commentators employ these terms. Yet they evidently have come to possess a subjective reality in the minds not only of commentators but of participants. How has this come to pass?
African Studies Seminar series. Paper presented 2 April, 1984
Keywords: Manyika (African people); Ethnic groups. Zimbabwe; Zimbabwe. Politics and government